Gold-nanorod enhances dielectric voltammetry detection of c-reactive protein: A predictive strategy for cardiac failure - Letchumanan, I; Arshad, MKM; Balakrishnan, SR; Gopinath, SCB (Elsevier Advanced Technology, 2024)
Indexed by WOS/ Scopus